Demand and supply of skills in Ghana : how can training programs improve employment and productivity? - Darvas, Péter; Palmer, Robert, 1978- (World Bank study., 2014)
Skills development in Ghana encompasses foundational skills, transferable/soft-skills, and technical and vocational skills. This report focuses on one segment of this skills development system: formal and informal technical and vocational education and training (TVET) at the pre-tertiary level. TVET represents a major intersection between education, youth and the labor market. The government has long promised to the population that increasing technical and vocational skills training opportunities will help solve youth unemployment. However, market distortions and inefficiencies have led to an adverse cycle of high costs, inadequate quality of supply and low demand, leading to further pressures on the effectiveness and efficiency of TVET services. This adverse cycle means that the political and policy promise of skills development helping to ease the unemployment problem is at risk of remaining unfulfilled. The report focuses on social and economic demand for (pre-tertiary) technical and vocational skills and maps out the supply of these skills from formal and informal, private and public sectors. The dual purpose has been to both carry out an institutional and policy analysis and also to establish a platform for monitoring sector performance and assisting policy and Development Partner harmonization. The report analyzes the economic and social demand for technical and vocational skills and the suitability of the current supply as well as the effectiveness of policy, coordination and financing of technical and vocational skills development. The report annex provides the summary of economic demand analyses from the key sectors reviewed and provides a full mapping of all technical and vocational programs in Ghana. The study offers a comprehensive set of policy recommendations for improving Ghana?s pre-tertiary technical and vocational skills development sector, which will be of interest to policy makers and development partners in Ghana.